2021
DOI: 10.1128/aem.00210-21
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Octenidine in a Simulated Sink Trap Environment Results in Selection of Pseudomonas aeruginosa, Citrobacter , and Enterobacter Isolates with Mutations in Efflux Pump Regulators

Abstract: Octenidine based disinfection products are becoming increasingly popular for infection control of multidrug resistant (MDR) Gram-negative isolates. When a waste trap was removed from a hospital and allowed to acclimatise in a standard tap rig in our laboratory, it was shown that Klebsiella pneumoniae, Pseudomonas aeruginosa, Citrobacter and Enterobacter spp. were readily isolated. This study aimed to understand the potential impact of prolonged exposure to low doses of a commercial product containing octenidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The CV solubilization assay therefore quantifies biofilm biomass, but cannot enumerate bacterial cells or indicate their viability. R2A agar was initially developed for enumeration and subculture of bacteria from potable water [98], and so we propose that R2A broth can serve as an appropriate medium for measuring biofilm formation in conditions most relevant to the sink trap and WPS as has been completed previously [99,100]. However, as mentioned in the Introduction, it is important to bear in mind that disposal of liquids and solids via sink traps will result in variable nutrient conditions and so there is no perfect laboratory model to mimic real-life sink traps or WPS.…”
Section: Discussionmentioning
confidence: 99%
“…The CV solubilization assay therefore quantifies biofilm biomass, but cannot enumerate bacterial cells or indicate their viability. R2A agar was initially developed for enumeration and subculture of bacteria from potable water [98], and so we propose that R2A broth can serve as an appropriate medium for measuring biofilm formation in conditions most relevant to the sink trap and WPS as has been completed previously [99,100]. However, as mentioned in the Introduction, it is important to bear in mind that disposal of liquids and solids via sink traps will result in variable nutrient conditions and so there is no perfect laboratory model to mimic real-life sink traps or WPS.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of antimicrobial resistance genes (ARGs) by mobile genetic elements such as conjugative plasmids can produce multi-drug resistant bacteria with the potential to cause intractable infections in immunocompromised patients. In human health settings, nosocomial infections have been associated with the colonisation of hospital sinks by multi-resistant organisms [ 11 ] and the exchange of genetic material between different bacterial species in these environments [ 12 ]. This is a particular concern with biocide-tolerant organisms that can persist in hospitals despite routine disinfection programs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all the lineages with these mutations presented decreased susceptibilities to β-lactams, quinolones, and sulfamethoxazole, whereas no significant cross-increased MICs of COL was observed ( Figure 2 , Table 2 and Table S1 ). Interestingly, Garrat et al [ 31 ] observed similar convergence of mutations in smvA and ramR in different Gram-negative species exposed to OCT, leading to decreased susceptibility to antibiotics.…”
Section: Resultsmentioning
confidence: 99%